NOVEL NANOCARRIERS FOR ETHNOPHARMACOLOGICAL FORMULATIONS - Sivapriya, V.; Ponnarmadha, S.; Azeezand, N. Abdul; Sudarshanadeepa, V. (International Journal of Applied Pharmaceutics, 2018)
A numerous novel drug delivery system has been emerged by combining herbal medicine with nanotechnology to administer drugs encompassing the enhancement of compatibility and efficacy. The herbal phytoconstituents are compatible compared to the chemical active pharmaceutical ingredients (APIs). But the therapeutic consequence of the phytoconstituent is limited due to poor aqueous solubility. Therefore, the demand to develop a system which improves the solubility of the phytomedicine is mounting rapidly. Nanotechnology plays a vital role in increasing the solubility, enhancing the bioavailability and improving the drug specificity of bioactive constituents. Nanosystems such as liposomes, nanoparticles, phytosomes, ethosomes, nanoemulsions and solid lipid nanoparticles are used to deliver the bioactive constituent at an adequate dose to the site of action and during the entire treatment period. The current review discusses the various novel drug delivery systems which have been developed to attain better therapeutic response of the herbal drug.